2006
DOI: 10.5194/npg-13-671-2006
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer shearing of a highly plastic clay

Abstract: Abstract. Shearing tests with a thin layer of clay between filter slabs render possible large and cyclic deformations with drainage. In the pressure range of 100 kPa they serve to validated visco-hypoplastic constitutive relations. This theory is also confirmed by tests with up to 14 MPa and super-imposed anti-plane cycles. After this kind of seismic disturbance the clay stabilizes if the ratio of permanent stresses is undercritical. Otherwise a spontaneous acceleration occurs after a delay. This could help to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Shear tests with thin layers of remoulded and consolidated saturated clay by Balthasar et al [1] exhibit features beyond those outlined by Terzaghi [24], as shown in Fig. 3.…”
Section: Water-saturated Soil With Critical Phenomenamentioning
confidence: 71%
See 2 more Smart Citations
“…Shear tests with thin layers of remoulded and consolidated saturated clay by Balthasar et al [1] exhibit features beyond those outlined by Terzaghi [24], as shown in Fig. 3.…”
Section: Water-saturated Soil With Critical Phenomenamentioning
confidence: 71%
“…On the other hand, the p w -neutrality of the mineral is sufficient for r 0 ij ¼ r ij À p w d ij by (1) to be the stress tensor of the solid fabric. In an experiment with a volume element of water-saturated soil, a quasi-static change of 1 3 r ii and of p w by the same amount would thus not change the state of the solid fabric, in particular its stress r 0 ij and void ratio e. In an equivalent experiment, r 0…”
Section: Water-saturated Soil In the Stable Rangementioning
confidence: 98%
See 1 more Smart Citation
“…Also, most of the latest published in-house developments have reported maximum forces of about 500 kN, pure mechanical loading and no dynamics [e.g. Gomez (2008); Geertsma (2002); Balthasar et al (2006); Kim et al (2006); Jiang et al (2004); Seidel and Haberfield (2002); Wong et al (2007)]. Superimposed dynamic testing and/or hydro-mechanical coupled testing was reported by Buzzi et al (2008) and Barla et al (2007Barla et al ( , 2010, but on significantly smaller samples and devices of quite different types.…”
Section: Introductionmentioning
confidence: 90%
“…Recently, the model has also been extended to clayey soil, e.g. [2,24,30,43]. Hypoplastic models have also been used to solve boundary value problems, e.g.…”
Section: Introductionmentioning
confidence: 99%